MAIN TYPES OF INTERACTIVE RUSSIAN LANGUAGE TEACHING METHODS IN AN ECONOMIC UNIVERSITY - Mamadaleva Feruza Alimjanovna, Kodirova Feruza Kakhramanovna (EPRA International Journal of Research and Development (IJRD), 2023)
In this article, the author focuses on modern methods of teaching the Russian language in non-linguistic universities and expresses certain scientific views. The demand for learning and teaching the Russian language is currently increasing. This encourages science teachers to take responsibility for their work.